Mortality from systemic erythematosus lupus in Brazil: evaluation of causes according to the government health database - Costi,Luisa Ribeiro (2017)
Abstract Objective: To characterize the causes of mortality in patients with systemic lupus erythematosus (SLE) in Brazil between 2002 and 2011. Methods: An exploratory ecological study of a time series using data from the Mortality Information System of DATASUS, the Department of the Unified Health System (Brazil's National Health System). Results: Brazil's SLE mortality rate was 4.76 deaths/105 inhabitants. The mortality rate was higher in the Midwest, North and Southeast regions than in the country as a whole. There were 6.3% fewer and 4.2% more deaths than expected in the Northeast and Southeast regions, respectively. The mean age at death was 40.7 ± 18 years, and 45.61% of deaths occurred between the ages of 20 and 39. Incidence was highest in women (90.7%) and whites (49.2%). Disorders of the musculoskeletal system and connective tissue were mentioned as an underlying cause of death in 77.5% of cases, and diseases of the circulatory system and infectious and parasitic diseases were also noted in fewer cases. SLE was mentioned as an underlying cause of death in 77% of cases, with no difference between the Brazilian regions (p = 0.2058). The main SLE-related causes of death were, sequentially, diseases of the respiratory and circulatory systems and infectious and parasitic diseases. Conclusions: This study identified a need for greater control of risk factors for cardiovascular diseases and a better understanding of the pathogenesis of atherosclerosis in SLE. Infectious causes are still frequent, and management should be improved, especially in the early stages of the disease.